Perancangan Sistem Pembelajaran Daring Menggunakan Model ADDIE - Akhmad Bakhrun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT The design of the online learning system is not only focused on the software aspect alone but also must pay attention to the teaching materials that will be managed to suit the characteristics and needs of students. This study designed an online learning system using the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). ADDIE is a model commonly used to design learning. The stages in this model are very similar to the Waterfall model in the field of software engineering. By using the ADDIE model, it is hoped that it will produce an online learning system that is in accordance with the pedagogical aspects of students and technologically in accordance with the concept of software development. The results of the system design are implemented using Moodle for database practicum lectures. Based on the learning outcomes, 100% of students passed the database practicum with an average level of understanding of 94.86%. In conclusion, the ADDIE model can be applied to design an online learning system according to the characteristics of students. Keywords: online learning system, ADDIE, waterfall, Moodle, database